Literature review and expert opinion on the treatment of high-risk acute myeloid leukemia in patients who are eligible for intensive chemotherapy - Palmieri, Raffaele; Billio, Atto; Ferrara, Felicetto; Galimberti, Sara; Lemoli, Roberto M.; Todisco, Elisabetta; Moretti, Federico; Venditti, Adriano (Frontiers in Oncology, 2024)
In patients with Acute Myeloid Leukemia (AML), the assessment of disease risk plays a central role in the era of personalized medicine. Indeed, integrating baseline clinical and biological features on a case-by-case basis is not only essential to select which treatment would likely result in a higher probability of achieving complete remission, but also to dynamically customize any subsequent therapeutic intervention. For young high-risk patients with low comorbidities burden and in good general conditions (also called "fit" patients), intensive chemotherapy followed by allogeneic stem cell transplantation still represents the backbone of any therapeutic program. However, with the approval of novel promising agents in both the induction/consolidation and the maintenance setting, the algorithms for the management of AML patients considered eligible for intensive chemotherapy are in constant evolution. In this view, we selected burning issues regarding the identification and management of high-risk AML, aiming to provide practical advice to facilitate their daily clinical management in patients considered eligible for intensive chemotherapy.